2007
DOI: 10.1002/cne.21327
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D4 receptor activation decreases the expression of μ‐opioid receptors in the rat striatum

Abstract: The dopaminergic and opioid peptide systems interact in many nuclei of the brain. In the striatum, dopamine/opioid peptide interactions modulate locomotor and motivated behaviors as well as reward, motivational, and tolerance processes in opiate dependence. Dopamine D(4) receptors (D(4) R) and mu-opioid receptors (MOR) are highly concentrated in the striosomes (islands) of the striatum, suggesting the existence of receptor-receptor interactions between them. In the present work we studied the role of D(4) R in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 64 publications
(61 reference statements)
1
22
0
Order By: Relevance
“…While D 1 R increases MOR density in the cell surface membrane by the formation of a D 1 R-MOR heteromer [40], genetic deletion of the D 2 R down-regulates MOR density [41]. We have previously demonstrated that acute D 4 R stimulation down-regulates MOR IR in the striosomes of the CPu, suggesting that D 4 R interacts with MOR promoting its internalization and degradation [26]. The participation of other D2-like receptors, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While D 1 R increases MOR density in the cell surface membrane by the formation of a D 1 R-MOR heteromer [40], genetic deletion of the D 2 R down-regulates MOR density [41]. We have previously demonstrated that acute D 4 R stimulation down-regulates MOR IR in the striosomes of the CPu, suggesting that D 4 R interacts with MOR promoting its internalization and degradation [26]. The participation of other D2-like receptors, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, contradictory results referred on MOR levels have been obtained in different regions of the CNS, including the CPu, from unchanged to increased expression [2325], which has been related to morphine sensitization. We have previously demonstrated that the acute activation of the dopamine D 4 receptor (D 4 R) decreases MOR immunoreactivity (IR) in the striosomal compartment of the CPu [26], where a high degree of co-localization between the two receptors exists [27]. Additionally, specific agonist activation of D 4 R prevents striatal acute and chronic morphine induced increases of several transcription factors (c-Fos, ΔFosB, and P-CREB) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It seems unlikely that the failure of PD 168,077 to induce nicotine-seeking behavior resulted from a low selectivity for DRD4, because the agonist has been demonstrated to be highly selective for DRD4, showing low binding affinities for other dopaminergic, adrenergic, or serotoninergic receptors (eg, with 4100-fold selectivity over DRD1, 4400-fold selectivity over DRD2, and 4300-fold selectivity vs DRD3) (Glase et al, 1997). It also seems unlikely that the failure of PD 168,077 to induce nicotine-seeking behavior resulted from an insufficient dosage as a similar range of doses has been used to elucidate the specific function of DRD4 in in vivo studies (Bernaerts and Tirelli, 2003;Gago et al, 2007;Nayak and Cassaday, 2003). Previously, it was reported that the role of both DRD1 antagonists and agonists in the reinstatement of cocaine-seeking behavior is dissociable in rats: a selective DRD1 antagonist, SCH23390, attenuates, whereas a selective DRD1 agonist has no affect on, the reinstatement of cocaine-seeking behavior in rats (Self, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for dopamine receptor and mu-opioid receptor cross-talk. Activation of D4 dopamine receptors decreases immunoreactivity for muopioid receptors in striosomes of the striatum (Gago et al, 2007). Furthermore, increasing dopamine concentration with methamphetamine decreases the mu-opioid receptor mRNA in SH-SY5Y neuroblastoma cells (Langsdorf & Chang, 2011).…”
Section: Potential Mechanisms Underlying Diet-induced Changes In Mu-omentioning
confidence: 99%